Diversity of mangrove-associated macroalgal epiphytes in Eastern Samar, Philippines - Josue, Shaira Lyle A.; Payo, Dioli Ann O. (2016)
Macroalgal epiphytes thrive on hard substrates like the pneumatophores, prop roots and trunks of mangroves. They are important members of the mangrove ecosystem because they act as primary producers that provide food and habitat for a number of organisms. This study aimed to determine the diversity and zonation patterns of mangrove-associated macroalgal epiphytes in General MacArthur, Eastern Samar, Philippines. Four sampling sites with three transect lines each were established. Mangrove pneumatophores were collected per transect line. Macroalgal samples were identified morphologically and anatomically using available taxonomic keys. Sixteen species were identified. Six species belonged to Rhodophyta, five to Chlorophyta, three to Phaeophyta and two to Cyanobacteria. No distinct horizontal pattern was observed however, results suggest that the distribution of the algal species within the sites is partially governed by their tolerance to desiccation. Some species such as Bostrychia tenella, and Caloglossa leprieurii are capable of withstanding longer periods of desiccation and were found to occur in higher frequencies in zones farther from the seaward margin.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.
Keywords: Science and technology